Short Androgen Suppression and Radiation Dose Escalation for Intermediate- and High-Risk Localized Prostate Cancer: Results of EORTC Trial 22991 - Bolla, Michel; Maingon, Philippe; Carrie, Christian; Villa, Salvador; Kitsios, Petros; Poortmans, Philip M P; Sundar, Santhanam; van der Steen-Banasik, Elzbieta M; Armstrong, John; Bosset, Jean-François; Herrera, Fernanda G; Pieters, Bradley; et al. (Journal of clinical oncology, 2016)
Up to 30% of patients who undergo radiation for intermediate- or high-risk localized prostate cancer relapse biochemically within 5 years. We assessed if biochemical disease-free survival (DFS) is improved by adding 6 months of androgen suppression (AS; two injections of every-3-months depot of luteinizing hormone-releasing hormone agonist) to primary radiotherapy (RT) for intermediate- or high-risk localized prostate cancer. A total of 819 patients staged: (1) cT1b-c, with prostate-specific antigen (PSA) ≥ 10 ng/mL or Gleason ≥ 7, or (2) cT2a (International Union Against Cancer TNM 1997), with no involvement of pelvic lymph nodes and no clinical evidence of metastatic spread, with PSA ≤ 50 ng/mL, were centrally randomized 1:1 to either RT or RT plus AS started on day 1 of RT. Centers opted for one dose (70, 74, or 78 Gy). Biochemical DFS, the primary end point, was defined from entry until PSA relapse (Phoenix criteria) and clinical relapse by imaging or death of any cause. The trial had 80% power to detect hazard ratio (HR), 0.714 by intent-to-treat analysis stratified by dose of RT at the two-sided α = 5%. The median patient age was 70 years. Among patients, 74.8% were intermediate risk and 24.8% were high risk. In the RT arm, 407 of 409 patients received RT; in the RT plus AS arm, 403 patients received RT plus AS and three patients received RT only. At 7.2 years median follow-up, RT plus AS significantly improved biochemical DFS (HR, 0.52; 95% CI, 0.41 to 0.66; P < .001, with 319 events), as well as clinical progression-free survival (205 events, HR, 0.63; 95% CI, 0.48 to 0.84; P = .001). In exploratory analysis, no statistically significant interaction between treatment effect and dose of RT could be evidenced (heterogeneity P = .79 and P = .66, for biochemical DFS and progression-free survival, respectively). Overall survival data are not mature yet. Six months of concomitant and adjuvant AS improves biochemical and clinical DFS of intermediate- and high-risk cT1b-c to cT2a (with no involvement of pelvic lymph nodes and no clinical evidence of metastatic spread) prostatic carcinoma, treated by radiation.